Characterisation And Performance Of Sno2 Film For Detection Of Volatile Organic Compounds Synthesised By Chemical Vapour Deposition Method - Tan, Xian-Ju (2013)
SnO2 films were successfully coated on alumina substrate by using tetramethyltin (TMT) as the precursor via chemical vapour deposition (CVD) technique, to be used as chemical sensor. Characterisation of the films was performed by using X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX) and field emission scanning electron microscope (FESEM). The sensor was optimised by varying parameters such as coating temperature (400 oC - 500 oC), coating time (30 min - 90 min) and annealing temperature (450 oC - 550 oC). The optimum coating condition was achieved at coating temperature of 450 oC and coating time of 60 min without annealing with highest sensitivity of 25.02 towards 500 ppm of ethanol vapour. It was also found that film thickness increased linearly from 0.31 μm to 16.77 μm as the coating time increased from 30 min to 90 min. Meanwhile, annealing temperature of 450 oC to 550 oC did not improve the sensitivity when compared to the sensitivity of the film without annealing. Instead, an increase of annealing temperature lowered the sensor sensitivity. The results also showed that response time decreased with increasing ethanol concentration meanwhile the recovery time increased with increasing ethanol concentration. The optimised sensor also responded to other volatile organic compounds (VOCs) such as acetone and methanol vapour.